2016
DOI: 10.2116/analsci.32.99
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Micro-Optics for Microfluidic Detection

Abstract: A method of embedding micro-optics into a microfluidic device was proposed and demonstrated. First, the usefulness of embedded right-angle prisms was demonstrated in microscope observation. Lateral-view microscopic observation of an aqueous dye flow in a 100-μm-sized microchannel was demonstrated. Then, the embedded right-angle prisms were utilized for multi-beam laser spectroscopy. Here, crossed-beam thermal lens detection of a liquid sample was applied to glucose detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Kazama et al. proposed and verified a novel method to embed the small‐size optics in a microfluidic device for thermal lens (TL) detection. Ottevaere et al.…”
Section: Detection In Microfluidic Flow Cytometrymentioning
confidence: 99%
See 1 more Smart Citation
“…Kazama et al. proposed and verified a novel method to embed the small‐size optics in a microfluidic device for thermal lens (TL) detection. Ottevaere et al.…”
Section: Detection In Microfluidic Flow Cytometrymentioning
confidence: 99%
“…Recently, Lin et al [127] reported a microfluidic system integrated with optical fibers for detection of phalaenopsis pathogens. Kazama et al [128] proposed and verified a novel method to embed the small-size optics in a microfluidic device for thermal lens (TL) detection. Ottevaere et al [129] presented a micro-optical system for ultraviolet (UV)/visible absorbance detection in silicon microfluidic channels.…”
Section: Optic-based Detectionmentioning
confidence: 99%
“…In addition, coaxially introduced lasers offer robust and simplified optics suitable for miniaturization. [15][16][17][18][19] The advantages of miniaturization include not only much-reduced instrument cost, but also greater compatibility with micro-/nanofluidic devices that can equip the ultrahigh sensitivity provided by TLM 20,21 with functions such as sample pretreatment, 22 fractionation, 23 parallel processing, 24,25 sequential fluid handling, 26,27 and microenvironment regulation. 28 Hence, a highly sought system of high specificity, sensitivity, throughput with enhanced temporal and spatial resolution may be formed by integrating TLM and micro-/ nanofluidics.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most popular materials for the analytical devices is polydimethylsiloxane (PDMS) [1,2]. By placing objects on the mold before casting the precursor liquid, optical parts such as prisms can be embedded in a PDMS microfluidic device for opto-fluidic applications [3][4][5].…”
Section: Introductionmentioning
confidence: 99%